The Fatal Shore, The Long Years, and the Geographical Unconscious. Considerations of Iconography, Chronology and Trade in Response to Negbi's 'The "Libyan" Landscape from Thera: A Review of Aegean Enterprises Overseas in the Late Minoan IA Period'. (10th February 2016) - Manning, Sturt; Monks, Sarah; Nakou, Georgia; De Mita Jr., Francis
Abstract : -